State regulation of business activity in fishery of Republic of Korea - Son Gun She (Известия ТИНРО)
Modern methods of state regulation of business activity in fishery of Republic of Korea are investigated, its efficiency is evaluated. The South Korean approaches to regulation of small business are compared with this practice in Russia. Korean creative approach to the state regulation of small business allows to use more effectively the limited resources and to increase their value added by means of the coastal regions involvement to the domestic and international tourist industry.